Curcumin affects function of Hsp90 and drug efflux pump of Candida albicans - Lee, Yean Sheng; Chen, Xinyue; Widiyanto, Tria Widiasih; Orihara, Kanami; Shibata, Hiroyuki; Kajiwara, Susumu (Frontiers in Cellular and Infection Microbiology, 2022)
Candida albicans is a pathogenic yeast that causes candidiasis in immunocompromised patients. The overuse of antifungal drugs has led to the development of resistance to such drugs by this fungus, which is a major challenge in antifungal chemotherapy. One approach to this problem involves the utilization of new natural products as an alternative source of antifungals. Curcumin, one such natural product, has been widely studied as a drug candidate and is reported to exhibit antifungal activity against C. albicans. Although studies of the mechanism of curcumin against human cancer cells have shown that it inhibits heat shock protein 90 (Hsp90), little is known about its function against C. albicans. In this paper, using a doxycycline-mediated HSP90 strain and an HSP90-overexpressing strain of C. albicans, we demonstrated that the curcumin triggered a decrease in Hsp90 by affecting it at the post-transcriptional level. This also led to the downregulation of HOG1 and CDR1, resulting in a reduction of the stress response and efflux pump activity of C. albicans. However, the inhibition of HSP90 by curcumin was not due to the inhibition of transcription factors HSF1 or AHR1. We also found that curcumin can not only decrease the transcriptional expression of CDR1, but also inhibit the efflux pump activity of Cdr1. Hence, we conclude that disruption of HSP90 by curcumin could impair cell growth, stress responses and efflux pump activity of C. albicans.